Three-dimensional Orbit and Dynamical Masses of GJ 105 AC - Cayla M. Dedrick; Jason T. Wright; Jason D. Eastman; Cullen H. Blake; Samson A. Johnson; Peter Plavchan; John Asher Johnson; David H. Sliski; Maurice L. Wilson; Robert A. Wittenmyer; Thomas Barclay; Jonathan Horner; et al. (The Astrophysical Journal)
The precision of stellar models is higher than the precision at which we are able to measure the masses of most stars, with the notable exception of binaries where we can determine dynamical masses of the component stars. In addition to well-measured stellar properties, the ideal benchmark star is far enough from its companion that its properties are indistinguishable from an otherwise identical single star. Currently, there are a handful of stars with precise (±3%), model-independent mass measurements that are “effectively single” and for which we can obtain clean spectra (i.e., spectra that are not blended with a close companion). In this paper, we introduce GJ 105 AC as the newest members of this exclusive population. We present an updated orbital analysis for the long-period K3+M7 binary GJ 105 AC. We jointly analyze radial velocity (RV) and relative astrometry data, including new RVs from the Miniature Exoplanet Radial Velocity Array that capture the full periapsis passage and the RV minimum of the 76.0 ± 1.3 yr orbit for the first time. We derive precise dynamical masses of M _1 = 0.78 ± 0.02 M _⊙ and M _2 = 0.098 ± 0.002 M _⊙ . We find that of all stars with similarly precise masses (∼2%), GJ 105 AC stands out as having the widest on-sky separation after α Centauri AB, making it one of the most easily accessible to spectroscopy, as well as the the second-widest true separation, ensuring that its members are truly “effectively single” in terms of their evolution.